Perception and Satisfaction on Flexible Learning Approach to Student’s Academic Achievement - Dinoy, Romar B.; Bantilan, Flora Mae A. (International Journal of English Literature and Social Sciences (IJELS), 2023)
Flexible learning has been used as an alternative approach in delivering instruction during the peak of the pandemic. In this regard, this study aims to determine the perception of flexible learning in three constructs: content delivery and activities of the module, process of teaching and teaching strategies; level of student satisfaction with flexible learning, and academic achievement. Also, it evaluates the correlation between the student's perception and satisfaction and their academic achievement. The researchers utilized a Likert scale survey questionnaire to assess the said variables. Data were statistically treated using mean, standard deviation, percentage, and Pearson Product-Moment of Correlation. The results show that the students have a positive perception of flexible learning and are absolutely satisfied with the course. It is also revealed that student satisfaction is statistically related to academic achievement. Thus, it is recommended to encourage educators to evaluate the satisfaction of the students with their learning regularly.